AKULTURASI HUKUM ADAT BADUY DENGAN HUKUM POSITIF INDONESIA - Suprih Irma Anggraini; Yulia Ulfa; Duddy Rivaldy (Rechtsregel : Jurnal Ilmu Hukum, 2020)
The Baduy tribe is one of the indigenous tribes that live in Indonesia. When compared to other indigenous tribes in Indonesia, the Baduy tribe is located closest to the capital city of the country. This is special to describe, how Baduy maintains its customs and customary laws in the midst of the influence of technological advances and the development of positive Indonesian law which is especially because of its geographical location not far from the metropolitan city, namely Jakarta and its surroundings. Then the purpose of this research is also to reveal how the Baduy people are bound or bind themselves to customary laws which among or some of them can be said to be inconflict with human rights law, such as the prohibition of formal education, prohibition of technological activities, prohibition of building proper community facilities according to their abilities. age, and other special rules that are not as free as the outside Baduy community in general. The patterns of behavior and social order in the Baduy customary community need to be identified together and carefully, whether the existence of Baduy custom is worth preserving completely and forever if there are rules that are not in accordance with Indonesian positive law such as relevance to the ideals of the nation and the law -State Law. Or it turns out that the clash of legal rules is actually a variation of a separate legal system for the benefit of the Indonesian State in general and for the Baduy indigenous people in particular